Benefits and Effectiveness of the KIP Lecture Program for Recipient Students in Accessing Education at Higher Education - Neysa Aulia,; Ruth Evelonia Hariani Siburian,; Zayna Hayani,; Hairani Siregar, (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
KIP-College is one of the Social Security programs that serves to help students who want to enter college by providing academic assistance. This program meets the living needs of students, especially for those who have a poor economic background or lack of resources to enter college. The purpose of the KIP-Kuliah program is to address the problem of poverty in the community by providing assistance to underprivileged students to attend college, meet their living needs during college, and prosper from educational and economic deprivation. To carry out this KIP-College program, a qualitative approach is used, which includes the process of observation, interviews, and documentation sessions as concrete evidence. This shows that although the KIP-College program is not well-targeted, it has met the needs of educationally and financially disadvantaged students to attend university.